Meningkatkan Hasil Belajar Siswa Pada Materi Ajar Listrik Statis Dengan Pendekatan Problem Posing - Helda yulianti; Syubhan An'nur; Mustika Wati (Universitas Lambung Mangkurat, 2014)
Based on interviews with a teacher of science at Junior High School 17 Banjarmasin are obtained that the result of student learning is still low. It is caused the pattern learning that takes place often using lecture method so that need to doing the research. The general objective of the research is to know the use of problem posing approach on static electricity subject to improve the result of student learning at IX grade in Junior High School 17 Banjarmasin. The specific objectives of the research are to describe (1) lesson plan adherence; (2) result of student learning; and (3) response of student towards learning. This research is a classroom action research of Kemmis and Mc Taggart model which consisting of two cycles in four times of meeting consisting of planning, action, observation, and reflection. Devices and instruments are used are the lesson plan, handout, student worksheet, result of learning test, lesson plan sheet, and response questionnaire. Analysis of data is used are quantitative and qualitative. The results of the research are (1) lesson plan adherence increased from the first cycle of 80,42%, and the second cycle of 87,11%; (2) the result of student learning classically completed from the first cycle of 85,71% and the second cycle of 90,47%; (3) respond questionnaire of student got well response. Be obtained the conclusion that the problem posing approach can improve the result of student learning at IX grade in Junior High School 17 Banjarmasin on static electricity subject.